Formation of CeO2 coatings on Si–SiC foams by electrophoretic deposition and sintering in air. Issue 12 (15th August 2019) - Spaggiari, Marco; Bianchi, Giovanni; Santoliquido, Oscar; Senn, Philippe; Fitriani, Pipit; De Hazan, Yoram; Penner, Dirk; Yoon, Dang-Hyok; Ortona, Alberto
Abstract: We demonstrate that AC-EPD, using an aqueous slurry system followed by sintering in air, is an effective technique to form thick ceramic coatings on porous Si–SiC cellular ceramic substrates. As an example, CeO2 particles with high surface area dispersed in water have been deposited successfully on Si–SiC foams by optimizing the zeta potential and dispersion conditions. Moreover, the parameters for AC-EPD were determined by controlling voltage, frequency, time, and degree of signal asymmetry to minimize water electrolysis in this aqueous system. The microstructure of CeO2 layer has been controlled by adjusting sintering conditions to obtain porous and dense layers at 1200 and 1400 °C, respectively. The grain growth of the CeO2 deposit upon the heat treatment was explained by the diffusion of SiO2 into the CeO2 coating layer, which resulted in a firm joining with the Si–SiC substrate.